(untitled) (Journal of Economic Research & Business Administration, 2015)
In given article theoretical aspects organizational-economic relations are considered at commercialization of objects of intellectual property in РК. The basic functions and powers of Committee on intellectual property rights of Ministry of Justice RK are presented, distribution on regions of the demands which have arrived from national applicants on delivery of security documents on inventions on years is analysed and on the basis of the spent analysis the basic problems of commercialization of intellectual property are revealed.